Debt-Related Vulnerabilities and Financial Crises - Setser, Brad.; Halikias, Ioannis; Pitt, Alexander; Rosenberg, Christoph (Washington, D.C. : International Monetary Fund, 2005)
The analysis of currency and maturity mismatches in sectoral balance sheets has increasingly become a regular element in the IMF's tool kit for surveillance in emerging market countries. This paper describes this so-called balance sheet approach and shows how it can be applied to detect vulnerabilities and shape policy advice. It also provides a broad-brushed overview of how balance sheet vulnerabilities have evolved over the past decade and cites a number of case studies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet